Tourism usage of digital collaborative economy platforms in Europe: situation, behaviours and implication for the digital policies - Adrián Mendieta-Aragón; Laura Rodríguez-Fernández; Julio Navío-Marco (International Telecommunications Society (ITS), 2023)
This research analyses how tourists using digital sharing economy platforms have behaved in the European Union, whether there are differences between European regions and how they have evolved with the pandemic. Using spatial econometric techniques, this study provides a comparative analysis, in space and time, that identifies regional inequalities in terms of the intensity of demand for accommodation offered on digital sharing economy platforms. In particular, different clusters of high intensity of collaborative tourism have been detected, and spatial spillover effects and interdependencies of European regions in collaborative tourism have been recognised, finding a positive spatial autocorrelation in the intensity rate of collaborative tourism. An effect of tourist destination saturation on the use of accommodation offered on digital sharing economy platforms has also been observed. Several digital public policy implications have been discussed, promoting regulatory coordination at the interregional and pan-European levels to avoid inequalities and imbalances across Europe.
Keywords: 330; Digital tourism; platforms' economy; digital policies; European regions; sharing; ESDA; spatial models